Pengaruh Penambahan Bakteri Asam Laktat dan Pakan Sumber Energi terhadap Kandungan Nutrisi dan Fraksi Serat Silase Pelepah Sawit - H. Suryani; W. Wijayandri; S. Fakhri; A. Latif; A. Yani (Jurnal Peternakan, 2020)
The purpose of this research was to evaluate the effects of Lactic Acid Bacteria (LAB) and the best energy-rich feed that could be combined with LAB on oil palm fronds (OPF) silage. Energy-rich feeds (molasses, rice polish, palm kernel cake (PKC), sludge and rice bran) were used and each of them was combined with LAB (Lactobacillus plantarum and Lactobacillus fermentum, 1010 CFU/mL). The treatments were : P0 = OPF, P1 = OPF + LAB (5 ml/kg), P2 = OPF + LAB (5 ml/kg) + molasses (3%), P3 = OPF (control) + LAB (5 ml/kg) + rice polish (3%), P4 = OPF + LAB (5 ml/kg) + BIS (3%), P5 = OPF + LAB (5 ml/kg) + sludge (3%), P6 = OPF + LAB (5 ml/kg) + rice bran (3%). Silages were packed in airtight transparent bottle silo (300 g capacity) and stored at room temperature. After 3 weeks, each silo was opened and sampled for physicals, nutrient and fiber analyses. Data were statistically analyzed in completely randomized design, and continued with orthogonal contrast analyses. The addition of LAB significantly (P<0.01) increased crude protein (CP), crude fibre (CF), acid detergent fibre (ADF), decreased hemicellulose but no significant effect on nitrogen-free extract (NFE) and neutral detergent fibre (NDF) content of OPF silages. The addition of energy-rich feeds significantly (P<0.01) increased CF and CP, decreased NFE, NDF and hemicellulose, but no significant effects on ADF of OPF silage. The most suitable energy-rich feeds combining with LAB in producing OPF silage was rice bran.